Ruralizzare l’uomo. Prospettive heideggeriane per un’etica dell’abitare - Pantaleone, Luca (Filosofia Morale/Moral Philosophy, 2025)
The Wohnunsfrage (the question of dwelling) occupies a central role within Heidegger’s philosophy, touching on various key points: from the relationship between man and language to that with technique, from the interpretation of the “thing” to the metaphysics and the history of being. The aim of this contribution is to investigate the perspectives that the Heideggerian idea of ​​dwelled space opens up in connection with the ethics and history of being, verifying its relationship with the principles of equality and identity in order to investigate the relation between the way of modern building and the culture/tradition of peoples in the globalized world.